Rheology of fresh cement pastes containing polymer nanoparticles. (June 2021) - Zhang, Chaoyang; Kong, Xiangming; Yin, Jianhao; Fu, Xiaochen
Abstract: Influences of polymer nanoparticles (PNPs) with varied charge densities on the rheological behaviors of fresh cement pastes (fcps) without and with polycarboxylate superplasticizer (PCE) were studied. In the blank fcp, the addition of PCE and highly anionically charged PNPs greatly decreases the yield stress and the plastic viscosity due to their large adsorption on cement that produces electrostatic repulsion and steric hindrance between cement grains. However, the non-adsorbing nonionic PNPs show a slightly opposite effect. In the PCE-containing fcp, both the anionic and nonionic PNPs become non-adsorbing on cement due to the stronger affinity of PCE to cement surface. In this way, the addition of the PNPs in the PCE-containing fcp slightly increases the yield stress and the plastic viscosity, but significantly decreases the pseudoplastic index, which is believed to result from the generation of the so-called depletion attractive force between cement grains induced by the non-adsorbing polymers.